2011
DOI: 10.1007/s00213-011-2447-5
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram stimulates dopamine release from noradrenergic terminals and potentiates cocaine-induced dopamine release in the prefrontal cortex

Abstract: We suggested that disulfiram, by removing NA-mediated inhibitory control on noradrenergic terminals, causes an unrestrained cocaine-induced DA release from those terminals in the mPF cortex. In the accumbens and caudate nuclei, "allogenic" DA concentration might be clouded by DA originated from dopaminergic terminals. The possible role of "allogenic" DA in disulfiram ability to prevent stress-induced reinstatement of cocaine seeking is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 65 publications
(78 reference statements)
1
43
1
Order By: Relevance
“…Recent in vivo microdialysis studies in rats found that disulfiram or nepicastat alone produced robust increases in extracellular DA levels (approximately 300% above baseline) within the prefrontal cortex (PFC) (Devoto et al, 2012(Devoto et al, , 2013, a terminal region of DAergic mesocorticolimbic projections known to play a prominent role in the abuse-related effects of cocaine (Wise, 2009). In contrast, neither DBH inhibitor altered basal DA levels within the nucleus accumbens (NAc).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vivo microdialysis studies in rats found that disulfiram or nepicastat alone produced robust increases in extracellular DA levels (approximately 300% above baseline) within the prefrontal cortex (PFC) (Devoto et al, 2012(Devoto et al, , 2013, a terminal region of DAergic mesocorticolimbic projections known to play a prominent role in the abuse-related effects of cocaine (Wise, 2009). In contrast, neither DBH inhibitor altered basal DA levels within the nucleus accumbens (NAc).…”
Section: Discussionmentioning
confidence: 99%
“…Because cocaine-induced increases in DA within the NAc rather than the PFC predominantly mediate the discriminative stimulus effects of cocaine (Callahan et al, 1997), it is not surprising that in the present studies, cocaine failed to generalize to either disulfiram or nepicastat. Importantly, our dose range (up to 100 mg/kg disulfiram and 56 mg/kg nepicastat) and pretreatment time (2 hours) were chosen based on our own previous work and the aforementioned microdialysis studies, which reported maximal increases in DA levels within the PFC and reductions of NE levels across multiple brain regions using these parameters (Schroeder et al, 2010;Devoto et al, 2012Devoto et al, , 2013. Thus, the experiments were optimized to detect the presence of a cocaine-like interoceptive stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has been discovered that disulfiram has a significant effect on noradrenaline and dopamine pathways (20). Possibly because of these effects of disulfiram, there are growing research findings indicating that disulfiram might be used safely for alcohol dependent individuals, who have comorbidities with cocaine dependence or pathological gambling (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Possibly because of these effects of disulfiram, there are growing research findings indicating that disulfiram might be used safely for alcohol dependent individuals, who have comorbidities with cocaine dependence or pathological gambling (20)(21)(22)(23). Disulfiram also can be used safely in combination with other medications treating alcohol dependence such as acamprosate, naltrexone and topiramate and it may be effective alone for adolescents with alcohol abuse and dependence.…”
Section: Introductionmentioning
confidence: 99%